Konsep Penginjilan Dalam Kisah Para Rasul 18:9-10 Sebagai Upaya Revitalisasi Penginjilan - Aris Elisa Tembay (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2020)
Salah satu tugas gereja dan orang percaya adalah pekerjaan misi. Misi adalah semua kegiatan yang bertujuan untuk mengabarkan kematian dan kebangkitan Yesus Kristus sebagai pengorbanan untuk penebusan dosa manusia serta jaminan hidup yang kekal dalam nama-Nya. Jadi pekerjaan misi adalah Pengabaran Injil/penginjilan.Selanjutnya gereja bukan hanya mempunyai misi, tetapi seluruh kehidupan gereja itu adalah misi. Tugas memberitakan Injil adalah tugas setiap orang percaya. Gereja yang kuat dan bersinar adalah gereja yang bersedia pergi memberitakan kasih Allah kepada dunia, sehingga dunia mengalami kasih Allah. Sehingga masa depan dunia ada ditangan gereja. Gereja haruslah memiliki hati Allah. Tugas gereja memuridkan dan mengutus para murid untuk melaksanakan Mandat Agung Kristus. Maka, memberitakan kabar baik segala perbuatan dan karya Allah adalah tugas semua orang yang telah menerima anugerah keselamatan. Benih Injil haruslah terpancar dari semua aspek kehidupan orang percaya. Gereja yang kuat dan bertumbuh adalah gereja yang terlibat dalam pelaksanaan misi Allah bagi dunia. One of the tasks of the church and believers is missionary work. Mission is all activities aimed at proclaiming the death and resurrection of Jesus Christ as a sacrifice for the atonement of human sins and the guarantee of eternal life in His name. So missionary work is evangelism / evangelism. Furthermore, the church does not only have a mission, but the whole life of the church is a mission. The task of preaching the gospel is the duty of every believer. A strong and shining church is a church that is willing to go to preach God's love to the world, so that the world experiences God's love. So that the future of the world is in the hands of the church. The church must have the heart of God. The task of the church is to make disciples and send disciples to carry out the Great Mandate of Christ. So, to preach the good news of all the deeds and works of God is the duty of all those who have received the gift of salvation. The seeds of the gospel must be emanated from all aspects of a believer's life. A strong and growing church is a church that is involved in carrying out God's mission for the world.